Women and Politics: Representation of Women in Political Parties - Budiana , Muhammad (SEAN Institute, 2023)
The purpose of this study is to investigate the status of women inside Indonesia's political parties and organizations. This study will analyze the profile of women's representation at the management level and candidate positions in elections using a qualitative approach and a descriptive method. Specifically, the study will focus on the United States. According to the findings of the survey, the percentage of women holding candidate roles remains dismally low, despite the fact that a number of political parties have taken steps to boost the number of women working in management positions. This research also demonstrates that there are institutional and cultural barriers that limit women's presence in politics. Some examples of these constraints include gender stereotypes, conventional female duties in the home, and restricted access to political resources. The implication of this finding is that political parties need to increase their efforts to increase the representation of women at all levels of leadership and promote gender equality in politics. This research contributes to the political representation literature and provides insights for policy makers and political practitioners on how to increase the representation of women in political parties in Indonesia..